A lethal pneumonia model of Acinetobacter baumannii: an investigation in immunocompetent mice. (April 2019) - Zeng, X.; Gu, H.; Cheng, Y.; Jia, K.-R.; Liu, D.; Yuan, Y.; Chen, Z.-F.; Peng, L.-S.; Zou, Q.-M.; Shi, Y.
Abstract: Objectives: Acinetobacter baumannii can cause severe nosocomial and community-acquired pneumonia. To study the pathogenesis of A. baumannii and to develop new treatments, appropriate mouse models are needed. Most reported mouse models of pulmonary A. baumannii infection are non-lethal or require mouse immunosuppression to enhance infection. These models are not suitable for studying host immune responses or evaluating immunotherapies. Methods: The virulence of 30 clinical isolates was assessed in mice. The most virulent isolate, SJZ24, was selected to develop a pneumonia model in immunocompetent mice. The cytokine mRNA expression in the lung was assessed with real-time PCR. The cell infiltration in bronchoalveolar lavage fluid (BALF) after SJZ24 infection was determined by flow cytometry. Vaccine efficacy was assessed using this model. Results: Intratracheal inoculation of SJZ24 (5 × 10 7 CFU) resulted in death in 100% of the mice (5/5). SJZ24-infected mice showed high bacterial burdens in blood and organs as well as severe lung-tissue damage. Infection with SJZ24 induced increased inflammatory cytokine expression in the lung and increased neutrophil infiltration in BALF. Immunization with inactivated whole cells of SJZ24 showed 100% protection (5/5) against A. baumanni infection in this model. Conclusions: We established a lethal pneumonia model in immunocompetent mice with hypervirulent A. baumannii isolate SJZ24. This model can be used to study the immune response to A. baumannii infection and to evaluate vaccine efficacy.